2011
DOI: 10.1038/ijir.2011.32
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between ED and depression among middle-aged and elderly men in Korea: Hallym aging study

Abstract: The baseline questionnaires included demographic and health history information. The age-adjusted prevalence of current depression by GDS (X18), of ED by IIEF-5 score (o18), and of concomitant ED and depression were 12.2%, 28.2% and 11.0%, respectively. GDS increased according to severity of ED, adjusted for age, marital status, education, smoking, alcohol, hypertension, regular exercise, total cholesterol level, fasting blood sugar, body mass index (Po0.001, by analysis of covariance). ED was strongly associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 33 publications
0
26
0
1
Order By: Relevance
“…In within-persons analyses, we observed that increases in depression scores were significantly associated with increases in erectile dysfunction, which is consistent with the literature. In the general population (Jeong et al, 2011; Lotti et al, 2012) and studies of opioid-dependent men (Hallinan et al, 2008; Quaglio et al, 2008), depressive symptoms are often associated with increased symptoms of erectile dysfunction. Although the exact mechanism for this is unknown, psychological causes have been postulated (Jeong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In within-persons analyses, we observed that increases in depression scores were significantly associated with increases in erectile dysfunction, which is consistent with the literature. In the general population (Jeong et al, 2011; Lotti et al, 2012) and studies of opioid-dependent men (Hallinan et al, 2008; Quaglio et al, 2008), depressive symptoms are often associated with increased symptoms of erectile dysfunction. Although the exact mechanism for this is unknown, psychological causes have been postulated (Jeong et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The most investigated MSDs included ED, various types of ED, ejaculation dysfunctions (PE and DE), and HSDD in both the Asian and European studies. A total of 19 Asian studies presented the prevalence of ED (Çayan et al, 2017;Chung et al, 2015;Ghalayini et al, 2010;Hao et al, 2011;Huang et al, 2014;Hwang et al, 2010;Jeong et al, 2011;Khoo et al, 2008;Kim et al, 2009;Liu et al, 2010;Permpongkosol et al, 2008;Quek et al, 2008;Rao et al, 2015;Tang et al, 2015;…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…A sample of 203 subjects aged between 45 and 74 years old was assessed through the administration of International Index of Erectile Function 5 (IIEF-5) and Geriatric Depression Scale (GDS), in order to define the presence of a relationship between depressive symptoms and ED severity. ED was shown to be closely linked to depressive symptoms, together with some factors such as life style, smoking, and alcohol [55]. …”
Section: Ed In Elderly Men Affected With Psychiatric Disordersmentioning
confidence: 99%